An Observational Study of Dermatoses in Adolescents and Their Impact on Quality of Life - Rutoo Polra; Mauli Shah; Dharmesh Parmar; Pragya A. Nair (Indian Journal of Paediatric Dermatology, 2025)
Background: Adolescence is the period ranging between 10 and 19 years of age. It is a critical phase of transition affected by various dermatological diseases. The psychological impact of conspicuous skin conditions on adolescents is well documented, provoking feelings of embarrassment and concerns about body image. Aims: This study aims to study various dermatoses in adolescent age group. Objectives: The objective is to study its impact on quality of life of patients. To compare the pattern of dermatoses across gender, and different phases of adolescent age group. Materials and Methods: This was an observational study conducted in department of dermatology for 16 months after approval from institutional ethics committee. All patients falling in age group (10–19 years) were recruited after taking written consent in their vernacular language. A detailed history of demographic data, complaints of patient, onset, duration, and progression of cutaneous lesions were recorded in a prestructured proforma. Clinical examinations (skin/hair/nail) were carried out and photographs were taken. Patient/Guardian were given a proforma of Dermatology Life Quality Index (DLQI)/Child DLQI to fill to assess impairment in quality of life in patients. Statistical analysis was done using STATA 14. Results: The study included a total of 312 patients falling in the age group of 10–19 years. Maximum of 121 patients were in late adolescence phase (38.7%) with male: female ratio of 1.05. Infectious condition was found in majority 114 (36.5%) patients, of which fungal infections were the most in 52 (45.6%) patients followed by arthropod-borne infection in 29 (25.4%) patients. Among noninfectious conditions (198, 63.5%), disorders of appendages were the most common group with 72 (36.3%) patients, of which acne vulgaris (63, 87.5%) was diagnosed in majority. CDLQI was calculated in maximum of 191 (61.2%) patients, while DLQI was calculated in 121 (38.7%) patients. The quality of life compared among gender showed no significant difference. The mean CDLQI score was found maximum in arthropod-borne infections (5.42) while the mean DLQI score was maximum in fungal infections (5.45). Conclusions: The present study showed the most common dermatosis in early adolescence was scabies while in mid-adolescence and late adolescence, it was acne. More than half of the patients had quality of life affected by their dermatoses.